“Sugerimos o corte”: as censuras das telenovelas Dancin’ Days e Água Viva em tempos de Estado Autoritário (1978-1980) - Silva, Gabriela Nascimento (2018)
The aim of the present dissertation is to analyses the censorship in two soap operas displayed by Rede Globo that reached high rating points, attracting the public with their relaxed scenarios and, in parallel, their dense dramas retracting family issues, moral values and upward mobility. Dancin’ Days and Água Viva were transmitted in the end of the Military Rule, in the years of 1978 and 1980, respectively. With a comparative approach, illustrating similarities and differences of censorships, the research intention is to identify and discuss agents that build the many social representations in the studied soap operas, inserted in a context of marketing expansion and, simultaneously, forced to attend to the highest pressions of the Government by preserving good moral. With the support of collected data – censured scripts, censors and network view and DVDs of the studied soap operas – the research, that has as it's main problematic the concern and interest of an authoritarian government about the soap operas, and the censorship through the narrative of Dancin' Days and Água Viva, will get the effort to clarify the symbolic contest of power on different moments from the government. In conclusion, the fundance of this work consists on the pertinence of understanding an era in which mostly is said about censorship and little's been researched about it. Therefore, it is of the utmost importance that further more studies are realized about soap operas, product that remains as a great influence on Brazilian people, studying the process of censorship and the use of soap operas as an instrument of repression of the Military Rule – even in the end of its command – hiding words, rallies, information’s and representations